Analisis Pengaruh Perencanaan Keuangan, Pengalaman Investasi dan Risk Tolerance Terhadap Keputusan Investasi Mahasiswa di Bandar Lampung - Hafidh, M.; Angelica Cindiyasari, Shiwi (DINASTI RESEARCH, 2024)
This research aims to test whether there is a significant influence between financial planning, investment experience and risk tolerance on students' investment decisions in Bandar Lampung. This research uses validity test, reliability test and multiple analysis to test the influence between independent variables and dependent variables with the help of SPSS. This research uses independent variables, namely financial planning, investment experience, risk tolerance and dependent variables, namely investment decisions. The results of this research prove that financial planning, investment experience, risk tolerance don’t have a significant influence on students' investment decisions in Bandar Lampung. While risk tolerance has a significant influence on students' investment decisions in Bandar Lampung.